Solution and Stability of the Multiquadratic Functional Equation - Xiaopeng Zhao; Xiuzhong Yang; Chin-Tzong Pang (Abstract and Applied Analysis)
We consider the multiquadratic functional equation. We establish its general solution and provide a characterization for this functional equation. Finally, we prove the Hyers-Ulam-Rassias stability of this functional equation.